Metal organic framework (ZIF-67)-derived hollow CoS2/N-doped carbon nanotube composites for extraordinary electromagnetic wave absorption - Yan, Jing; Huang, Ying; Han, Xiaopeng; Gao, Xiaogang; Liu, Panbo (Composites. Part B, Engineering, 2019)
The hierarchical hollow framework involving interconnected highly conductive N-doped carbon nanotube networks and CoS2 particles were successfully prepared by metal-organic framework (MOF) derived method. After the two pyrolysis process in the atmosphere of reducing gas and inert gases, numerous carbon nanotubes interlaced on the surface of framework and CoS2 nanoparticles also attached on the surface. The electromagnetic parameters of CoS2/NCNTs composites can be well controlled by regulating the loadings of sample in sample-paraffin mixture. The results demonstrate that CoS2/NCNTs with 50% loadings show superior electromagnetic wave absorption properties in the wide frequency range, almost covering the whole X bands (8–12 GHz) only with a relative thin thickness of 1.6 mm. Hierarchical hollow structure and better impedance matching performance between N-doped carbon nanocube and CoS2 nanoparticles contribute to the enhancement of microwave absorption ability. Our work confirms that hollow framework CoS2/NCNTs composites can provide a novel idea for designing high-absorbability microwave absorbers.